GROWTH AND DEVELOPMENT PATTERN OF BARLEY VARIETIES AS INFLUENCED BY DATE OF SOWING AND NITROGEN LEVELS - SOORAJ CHANDRA PANKAJ; PAWAN KUMAR SHARMA; H. D. CHOUKSEY; S. K. SINGH (The Bioscan, 2015)
A field experiment was conducted at research farm, Department of Agronomy, Punjab Agricultural University, Ludhiana during rabi season 2012-13. A set of 27 treatment combinations including three dates of sowing viz. 16th October (D1), 15th November (D2) and 15th December (D3) in main plot, three varieties; PL 172, PL 426 and PL 807 in sub plot and three nitrogen levels; 75, 100 and 125 per cent of recommended dose of nitrogen (RDN 62.5 kg/ha) in sub-sub plot were evaluated. Treatments were replicated thrice as per split-split plot design. Crop sown on D1 attained significantly higher (plant height, dry matter accumulation at harvest). Crop sown on D3 attained significantly higher crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) at harvest. Varieties PL 807 performed better than all other varieties for growth parameters (plant height and dry matter accumulation) and growth pattern (CGR, RGR NAR). Application of 125 per cent of RDN resulted in improvement in most of the growth parameters (plant height, dry matter production and LAI) and growth pattern (CGR, RGR NAR). Crop sown on 16th October took more number of days from sowing to heading than other dates of sowing, thus it availed longest vegetative phase.